Involuntary psychiatric hospitalizations in Israel 2001–2018 and risk for immigrants from different countries. (July 2021) - Youngmann, Rafael; Goldberger, Nehama; Haklai, Ziona; Pugachova, Inna; Neter, Efrat
Highlights: Rates of 1st voluntary psychiatric hospitalization decreased between 2001 and 2014. Rates of 1st involuntary psychiatric hospitalization (IPH) were higher since 2011. Ethiopian immigrants had higher rates of IPH. This may reflect low SES and culture gap, which increase their vulnerability. Minority status and immigration are not necessarily a risk factor for IPH. Abstract: Since 2000, the Israeli mental health system has undergone a reduction in hospital beds, initiation of community-based rehabilitation, and transfer of governmental services to health maintenance organizations. This study examined trends, predictors and outcomes of involuntary psychiatric hospitalizations (IPH), in particular for immigrants. All first psychiatric hospitalizations of adults, 2001–2018, in the National Psychiatric Case Registry were used. Involuntary and voluntary hospitalizations were analyzed by demographic and clinical characteristics, and age-adjusted rates calculated over time. Multivariate logistic regression models were used to investigate IPH predictors and first IPH as a risk factor for one-year suicide after last discharge, and a Cox multivariate regression model to examine its risk for all-cause mortality. Among 73, 904 persons in the study, age-adjusted rates of IPH were higher between 2011 and 2015 and then decreased slightly until 2018. Ethiopian immigrants had the highest risk for IPH, immigrants from the former Soviet Union a lower risk, and that of Arabs was not significantly different, from non-immigrant Jews. IPH was not significantly associated with one-year suicide or all-cause mortality. These findings demonstrate the vulnerability of Ethiopian immigrants, typical of disadvantaged immigrants having a cultural gap with the host country and highlight the importance of expanding community mental health services.